Wahrnehmungspsychologische Analyse der Radfahraufgabe. - Platho, Christina; Paulenz, Andrea; Kolrep, Harald (My University, 2016)
Im Rahmen einer Analyse der Radfahraufgabe unter wahrnehmungspsychologischen Gesichtspunkten ließ die Bundesanstalt für Straßenwesen (BASt) untersuchen, wie Radfahrer ihre Verkehrsumwelt visuell und akustisch erfassen. Das Wissen um typische Wahrnehmungsmechanismen ermöglicht eine Optimierung künftiger Verkehrssicherheitsmaßnahmen.

In response to the high number of road traffic accidents involving cyclists, the Federal Highway Research Institute (BASt) has initiated a number of new research approaches. In a study using perception psychology to analyse the task of riding a bicycle, the BASt examined ways in which cyclists visually and acoustically comprehend their traffic environment. The knowledge acquired regarding typical mechanisms of perception allows for the optimisation of future road safety measures. The studies carried out by the BASt highlight the necessity of developing a deeper understanding of cyclists' typical visual and acoustic perception processes. There are grounds for believing that the existing traffic environment exacerbates the difficulty cyclists experience in assimilating information and adequately perceiving the situation in which they find themselves. Training programmes, campaigns and adjustments to the road traffic infrastructure, for example, could contribute to supporting cyclists' perceptive abilities, thereby allowing them to improve their judgement of traffic situations.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Forschungsprojekt; Wahrnehmungspsychologie; Verkehrspsychologie; Radverkehr; Unfallanalyse